Developing Progressive Engineering Curriculum for Global Acceptance and Sustainability - Rathi, Sheetal; Mishra, B. K.; Nirgude, Vaishali (Journal of Engineering Education Transformations, 2025)
Engineering education of the 21st century demands to be knowledge-based with rich innovation and value creations. On graduation, one should have an engineering career of 40 years. Therefore, learners shall develop the needful KSA and ACM who can not only do the traditional and routine jobs but also give the vision, create new avenues, create new jobs, help the industry to diversify the activities for sustainability, and provide the individual a lifelong career. It demands an evolving curriculum that should not only comply with the university curriculum but also fulfill the needs of the hour by providing flexibility, acceptability, and agility. TCET understands the needs and hence always strives to bring excellence and relevance to the curriculum. Being autonomous from A. Y. 2019-20 onwards, the college has the freedom to design its own curriculum, not only trying to comply with the requirements of affiliated universities but also trying to achieve global excellence in the field of technical education. The revision cycle has been set for three years. The curriculum highlights that practical & practice-based learning, problem & project-based learning, industry & research orientation, and pedagogy supplemented with andragogy & heutagogy have made the curriculum unique. The strategy and approach for curriculum design have not only made the institute achieve various compliances but also made the curriculum evolutionary and well-accepted by stakeholders including industry.